Severe acute malnutrition among under-5 children in low- and middle-income countries: A hierarchical analysis of associated risk factors (2020)
Objectives: Malnutrition is one of the main reasons for death among children <5 years of age in low- and middle-income countries (LMICs). It accounts for about one-third of preventable deaths among children. Reduction of malnutrition, especially severe acute malnutrition (SAM), is critical, directly or indirectly, to a targeted decrease in child mortality and improvement in maternal health. It would also help achieve sustainable development goal 2 (improvement of nutrition across the board) and sustainable development goal 3 (ensuring healthy lives and well-being promotion for all at all ages). The aim of this study was to develop and test a model of risk factors associated with SAM among under-5 children in LMICs. Methods: We used 51 recent demographic and health-surveys, cross-sectional, nationally representative data collected between 2010 and 2018 in LMICs. We used multivariable Bayesian logistic multilevel regression models to analyze the association between individual compositional and contextual risk factors associated with SAM. We analyzed information on 532 680 under-5 children (level 1) nested within 55 823 communities (level 2) from 51 LMICs (level 3). Results: The prevalence of SAM ranged from 0.1% in both Guatemala and Peru to 9.9% in Timor-Leste. Male children, infants, low birth weight children, children whose mothers had no formal education, those from poorer households, and those with no access to any media were more likely to have SAM. Additionally, children from rural areas, neighborhoods with high illiteracy and high unemployment rates, and those from countries with high intensity of deprivation and high rural population percentage were more likely to have SAM. Conclusion: Individual compositional and contextual factors were significantly associated with SAM. Attainment of sustainable development goals 1, 4, and 10 will automatically contribute to the eradication of SAM, which in turn leads to the attainment of sustainable development goals 2 and 3. These findings underscore the need to revitalize existing policies and implement interventions to rescue and prevent children from having SAM at the individual, community, and societal levels in LMI.